The occurrence of depressive symptoms in rheumatoid arthritis: a cross-sectional study - Golubović, Sonja; Ilić, Tatjana; Golubović, Boris; Gajić, Milica; Gajić, Zoran (Vojnosanitetski pregled, 2023)
Background/Aim. Depression, as a common comorbidity in patients with rheumatoid arthritis (RA), has been found to affect the disease diagnosis and treatment response. Accordingly, the aim of the study was to investigate the occurrence of depressive symptoms among patients with RA and the association between RA and depression. Methods. The cross-sectional study included 69 patients with RA. The depressive symptoms in patients with RA were assessed using the Beck Depression Inventory (BDI), and RA activity was measured by Disease Activity Score-28 for RA with erythrocyte sedimentation rate (DAS28-ESR) and Clinical Disease Activity Index (CDAI). Results. It was found that 42% of respondents reported having depressive symptoms of different severity, among which the majority (23.2%) presented with mild symptoms. A mild positive correlation was found between the BDI and the DAS28-ESR (r = 0.39 p = 0.001), as well as between the BDI and the CDAI (r = 0.40 p = 0.001). Place of residence (t = -2.14 p = 0.03) and employment status (t = -2.81 p = 0.00) associated with depressive symptoms were also found to have statistically significant differences within the group of respondents. In addition, age had a positive correlation with the disease activity, as well as the place of residence and employment status. Conclusion. It has been observed that depressive symptoms in patients with RA were associated with disease activity, employment status, and place of residence. Therefore, there is an important need for integrating rheumatologic and mental health services for future research toward a better understanding of both depression and RA.